Co-firing simulations with blending of low range coal and medium range coal on the performance of 615 MW capacity steam power plant and Indonesia carbon trading review - Apriliana Margawadi Kenanga; Widayat; Widodo Agung Suedy Sri (E3S Web of Conferences)
In Indonesia, coal-fired power plants (CFPP) account for nearly 70% of the nation’s electricity supply, contributing significantly to global warming. Biomass co-firing program for CFPP offers a potential solution. This study analyzes the impact of co-firing between blending of Low Rank Coal (LRC) with Medium Rank Coal (MRC) and wood pellet biomass, on the performance of 615 MW capacity CFFP. Using simulations with Cycletempo software, the research examines operational parameters such as plant efficiency, the performance of auxiliary equipment, and a techno-economic analysis focusing on carbon trading. The biomass co-firing tested reached up to 50%, with results indicating that increasing biomass content tends to reduce overall plant efficiency. Results indicate that at 100% load, the plant can accommodate up to 10% biomass co-firing, and at 75% load, it can handle up to 30%. Co-firing beyond 30% requires increased pulverizer power for stable operation. From techno-economic perspective, while co-firing reduces greenhouse gas emissions and generates benefits from carbon trading, the operational costs associated with fuel under co-firing are not yet fully profitable. This study offers guidance on increasing the co-firing ratio as part of the energy transition towards net zero emissions 2060 and provides recommendations for optimizing fuel mixtures in CFFP.